Protein Functionalization Revised: N‐tert‐butoxycarbonylation as an Elegant Tool to Circumvent Protein Crosslinking. Issue 15 (18th June 2014) - Van Nieuwenhove, Ine; Stubbe, Birgit; Graulus, Geert‐Jan; Van Vlierberghe, Sandra; Dubruel, Peter
<x xml:space="preserve">Abstract</x> The protection of primary amines available in proteins holds great potential to introduce a plethora of diverse functionalities along the protein backbone (e.g., via its carboxylic acid or alcohol moieties) while circumventing the crosslinking issue using conventional approaches. This paper reports on a straightforward and efficient proof‐of‐concept including the chemoselective N‐tert‐butyloxycarbonylation of the primary amines in the protein gelatin (gel‐NH‐BOC), followed by introducing crosslinkable methacrylamide moieties. The reaction is performed successfully under relatively mild conditions (50 °C). Following selective protein functionalization, the deprotection is realized by adding a catalytic amount of an aqueous hydrogen chloride solution. The present communication illustrates the occurrence of a straightforward and selective deprotection procedure, which is typically required to circumvent the occurrence of acidic hydrolysis of the protein backbone. The results hold promise for a large range of biomedical applications in which the presence of primary amines is essential for preserving the biological activity. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>